Durable Physiological Changes and Decreased Syncope Burden 12 Months After Unifocal Right-Sided Ablation Under Computed Tomographic Guidance in Patients With Neurally Mediated Syncope or Functional Sinus Node Dysfunction. (17th May 2021) - Debruyne, Philippe; Rossenbacker, Tom; Janssens, Luc; Collienne, Christine; Ector, Joris; Haemers, Peter; le Polain de Waroux, Jean-Benoît; Bazelmans, Christine; Boussy, Tim; Wijns, William
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cardioneuromodulation is a cardioneuroablative approach aiming to create adequate vagolysis of the sinoatrial node through partial ablation of the anterior right ganglionated plexus. Methods: We performed an interventional study in patients with recurrent neurally mediated syncope (group A) or functional sinus node dysfunction (group B). Syncope burden, ECG, 24-hour rhythm data, tilt table test, exercise test, and pharmacological challenge with atropine were assessed at baseline and at regular intervals to 12 months. Results: Fifty patients (31 in group A and 19 in group B) underwent cardioneuromodulation. The mean number of syncopes during the previous 12 months was 9.7±18.2. The procedure was associated with a lower rate of syncope (−95%) and presyncope (−95%) at 12 months versus baseline ( P <0.001). Thirty-seven patients remained entirely free of syncope at 12 months, and the syncope-free survival curve remained stable between the 12- and 30-month follow-up. After a mean ablation time of 8±4 minutes, the P-P interval shortened by 247±146 ms ( P <0.001). Basal heart rate (HR) increased by 18% ( P <0.001) and remained stable between 6 and 12 months. At 12 months, the mean HR increased by 12% in the entire cohort ( P <0.001), reached 23% in patients with baseline mean HR <70 beats per minute ( P <0.01), and did not increase in patients with baseline HR >70 beats per minute. Maximum HR during exercise decreased by 10 beats per minute at 1 month ( P <0.001) and was restored at 12 months. Conclusions: Cardioneuromodulation is a safe and fast treatment giving rise to a long-term partial sinus node vagolysis with no apparent short- or long-term safety concerns or undesirable persisting modifications of the intracardiac autonomous nervous system. The impact on vasoplegia is less clear. Cardioneuromodulation is associated with a good clinical outcome in most patients with neurally mediated syncope or functional sinus node dysfunction. These promising data require confirmation in a multicenter randomized trial. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02954666.